Comparative Structural and Antigenic Characterization of Genetically Distinct Flavobacterium psychrophilum O-Polysaccharides - Cisar, John O.; Bush, C. Allen; Wiens, Gregory D. (Frontiers in Microbiology, 2019)
Little is known about the underlying basis of serotype specificity among strains of Flavobacterium psychrophilum, the agent of rainbow trout fry syndrome and bacterial cold-water disease. The identification of different heat-stable O-serotypes among strains of this gram-negative pathogen does however suggest structural variations in the O-polysaccharide (O-PS) moiety of cell surface lipopolysaccharide (LPS). A trisaccharide composed of L-Rha, L-FucNAc and D-Qui2NAc4NR, where R represents a dihydroxyhexanamido derivative, was previously identified as the repeating unit of Fp CSF259-93 O-PS. Interestingly, the O-PS gene cluster of this strain and that of Fp 950106-1/1, which belongs to a different O-serotype, are identical except for wzy, which encodes the putative polymerase that links trisaccharide repeats into O-PS chains. We have now found from results of glycosyl composition analysis and high-resolution nuclear magnetic resonance, that the linkage of D-Qui2NAc4NR to L-Rha, which is α1-2 for Fp CSF259-93 versus β1-3 for Fp 950106-1/1, is the only structural difference between O-PS from these strains. The corresponding difference in O-serotype specificity was established from the reactions of rabbit and trout anti-F. psychrophilum antibody with purified O-PS and LPS. Moreover, LPS-based differences in antigenicity were noted between strains with O-PS loci identical to those of Fp CSF259-93 or Fp 950106-1/1, except for the genes predicted to direct synthesis of different R-groups in Qui2NAc4NR. The findings provide a framework for defining the genetic basis of O-PS structure and antigenicity and suggest that the repertoire of F. psychrophilum O-serotypes extends beyond what is presently recognized from serological studies of this important fish pathogen.